Evaluation of the physical and chemical characteristics of waste excavated from an open dump site for sustainable waste management - Reba Anindyajati Pratama; Sri Wahyono; Firman Laili Sahwan; Feddy Suryanto; Muhammad Hanif; Wiharja; Prihartanto; Prasetiyadi; Suprapto; Regina Dea Tilottama; Sarkiwan; Diyono (Case Studies in Chemical and Environmental Engineering)
Waste management is a global concern with significant environmental and socio-economic impacts. In Indonesia, particularly in Serang City, challenges in waste processing are prevalent. This study explores the characteristics of waste and potential valorization strategies at the Cilowong disposal site. It involves sampling, physical and chemical composition testing, and nutrient content analysis. The waste density analysis reveals consistent values similar to other regional landfills. Fractionation indicates that materials under 10 mm have higher densities than those over 10 mm, with plastics dominating the larger fraction. Specifically, materials over 10 mm account for 59.88%, while those under 10 mm comprise 40.12%. The composition analysis highlights a high proportion of unsorted residual waste and plastics, with compost and biowaste showing decomposition. Notably, challenges in meeting standards for Refuse Derived Fuel (RDF) and compost quality highlight the necessity for pretreatment. The caloric value of the waste is 2,158 Kcal/kg, with a moisture content of 42.45% and ash content of 56.21%. Despite these values, the waste from Cilowong shows potential for RDF production and waste-to-energy applications. However, 1 mg/kg mercury contamination in compost raises concerns about its suitability for food crops. The fine fraction from landfill mining could serve alternative purposes, such as soil cover and environmental remediation. Effective waste valorization strategies are essential for improving landfill capacity and creating sustainable waste management solutions, especially for larger (>10 mm) and smaller (<10 mm) waste fractions.